THE RESPONSIBILITIES OF THE GUARDIANSHIP COUNCIL IN CASES OF PARENTAL ALIENATION (ESMAT Magazine, 2019)
This article seeks to analyze the responsibilities of the guardianship council in cases of parental alienation, to the detriment of the healthy development of the child and the adolescent and in disagreement with the theory of integral protection. Through the hypothetical-deductive method, technique of bibliographical research, and deductive methodology, the aim is to clarify the attributions of the tutelary council and which procedures should be adopted in the hypothesis of parental alienation, in order to avoid greater losses of affectivity and development of the child and the Adolescents and to preserve the rights of children and adolescents. We used books of legal scholars and applicators of Law and Social Service, as well as jurisprudential understandings, as an example, on the subject.